Targeting High Mobility Group Box-1 (HMGB1) Promotes Cell Death in Myelodysplastic Syndrome - Kam, Angel Y.F. (Clin Cancer Res, 2019)
PURPOSE: Myelodysplastic syndrome (MDS) is associated with a dysregulated innate immune system. The purpose of this study was to determine whether modulation of the innate immune system via high mobility group box-1 (HMGB1) could reduce cell viability in MDS. EXPERIMENTAL DESIGN: We quantified HMGB1 in a MDS cell line MDS-L and in primary MDS cells compared to non-malignant hematopoietic cells. We performed loss-of-function studies of HMGB1 using pooled siRNAs and a small molecule inhibitor sivelestat compared to standard chemotherapy. We measured levels of engraftment of MDS-L cells in NOD-scidIL2Rg(null) (NSG) mice following treatment with sivelestat. Mechanistically, we interrogated cell survival pathways and 45 targets within the NFκB pathway using both protein analysis and a proteome profiler array. RESULTS: We discovered that HMGB1 had increased expression in both MDS-L cells and in primary CD34+ MDS cells compared to healthy CD34+ hematopoietic cells. Sivelestat impaired MDS cell expansion, increased cellular death, and spared healthy hematopoietic cells. MDS-L marrow engraftment is reduced significantly at 17 weeks following treatment with sivelestat compared to control mice. Treatment of CD34+ MDS cells with sivelestat and azacitidine or decitabine were additive to increase apoptotic cell death compared to chemotherapy alone. Sivelestat promoted apoptosis with increased expression of PUMA, activated caspase 3, and increased DNA double-strand breaks. Inhibition of HMGB1 reduced levels of toll-like receptors (TLRs) and suppressed activation of NFκB in MDS-L cells. CONCLUSIONS: Inhibition of HMGB1 could promote MDS cell death and alter innate immune responses via suppression of NFκB pathways.